If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5x + -2 = x + -2 Reorder the terms: -2 + -5x = x + -2 Reorder the terms: -2 + -5x = -2 + x Add '2' to each side of the equation. -2 + 2 + -5x = -2 + 2 + x Combine like terms: -2 + 2 = 0 0 + -5x = -2 + 2 + x -5x = -2 + 2 + x Combine like terms: -2 + 2 = 0 -5x = 0 + x -5x = x Solving -5x = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -5x + -1x = x + -1x Combine like terms: -5x + -1x = -6x -6x = x + -1x Combine like terms: x + -1x = 0 -6x = 0 Divide each side by '-6'. x = 0 Simplifying x = 0
| 20x+35x=121 | | 5-2(x+2)=13 | | 14x-3+30=16x+11 | | x/3*4=20 | | 95=8x-8 | | 5+2(3x-8)=2x+9 | | 11+d+(-4)ford=-6 | | k^2-32k+8=0 | | 3(8.2-x)=6.6 | | -2(3x-2)=4-6x | | 26=6(5-a)+2 | | 7*5=63-N | | x/34=20 | | 56=t-25 | | 12x+11+69=25x+2 | | -5x-4=-3x+10 | | -10p-8=2 | | 3x+10y=-4 | | 63x^3+108x^2+81x= | | 2u-3=3 | | 6x+7=-2+7x | | 7x^2+12x+9= | | 7x-4(x+5)=16 | | x-10=-38+5x | | 42x^2-41x-8=0 | | 31+25x=-5-5 | | 7x^2+12x+9=0 | | -3x-10=70+5x | | 9x+108-8=11x | | w-1=1 | | -8(x-4)=-32 | | 5x-11=8x+25 |